Early M‐Protein Dynamics Predicts Progression‐Free Survival in Patients With Relapsed/Refractory Multiple Myeloma. Issue 6 (17th July 2020) - Yan, Xiaoyu; Xu, Xu Steven; Weisel, Katja C.; Mateos, Maria‐Victoria; Sonneveld, Pieter; Dimopoulos, Meletios A.; Usmani, Saad Zafar; Bahlis, Nizar J.; Puchalski, Thomas; Ukropec, Jon; Bellew, Kevin; Ming, Qi; et al.
Abstract : This study aimed to predict long‐term progression‐free survival (PFS) using early M‐protein dynamic measurements in patients with relapsed/refractory multiple myeloma (MM). The PFS was modeled based on dynamic M‐protein data from two phase III studies, POLLUX and CASTOR, which included 569 and 498 patients with relapsed/refractory MM, respectively. Both studies compared active controls (lenalidomide and dexamethasone, and bortezomib and dexamethasone, respectively) alone vs. in combination with daratumumab. Three M‐protein dynamic features from the longitudinal M‐protein data were evaluated up to different time cutoffs (1, 2, 3, and 6 months). The abilities of early M‐protein dynamic measurements to predict the PFS were evaluated using Cox proportional hazards survival models. Both univariate and multivariable analyses suggest that maximum reduction of M‐protein (i.e., depth of response) was the most predictive of PFS. Despite the statistical significance, the baseline covariates provided very limited predictive value regarding the treatment effect of daratumumab. However, M‐protein dynamic features obtained within the first 2 months reasonably predicted PFS and the associated treatment effect of daratumumab. Specifically, the areas under the time‐varying receiver operating characteristic curves for the model with the first 2 months of M‐protein dynamic data were ~ 0.8 and 0.85 for POLLUX and CASTOR, respectively. Early M‐protein data within the first 2 months can provide a prospective and reasonable prediction of future long‐term clinical benefit for patients with MM.